(untitled) (Innovative professional education, 2024)
The partnership in the field of professional and professional higher education between Germany and Ukraine is not only an example of cooperation between the two countries, but also a key element in the formation of modern educational approaches and the training of qualified specialists for the global labor market. This partnership is marked by the exchange of best learning methods, innovative programs and the opportunity to improve the qualifications of students in the field of hospitality, hygiene and master of industry or production, focusing on the history of the partnership, the main programs and initiatives, as well as the impact of this collaboration on the development of both countries in the modern world.